Future risk of falls induced by ankle-foot sprains history: An observational and mendelian randomization study - Xiao'ao Xue; Weichu Tao; Qianru Li; Yi Li; Yiran Wang; Le Yu; Xicheng Gu; Tian Xia; Rong Lu; Ru Wang; He Wang; Yinghui Hua (Sports Medicine and Health Science)
Background: Ankle-foot sprains are the most common musculoskeletal injuries, which can impair balance and theoretically increase the risk of falls, but still, there is a lack of evidence supporting the direct association between ankle-foot sprains and the future risk of falls. Methods: UK Biobank cohort was utilized to measure the association between ankle-foot sprains and fall risk with covariates adjusted. Then, the two-sample Mendelian randomization (MR) analysis was applied based on the genetically predicated ankle-foot sprains from FinnGen to validate causal relationship. Finally, genetically predicated cerebellar neuroimaging features were used to explore the mediating role of maladaptive neuroplasticity between ankle-foot sprains and falls by two-step MR analyses. Results: Patients with ankle-foot sprains history exhibited a slightly increased risk of falls than the matched controls before and after adjustment for covariates (odd ratio [OR] ranged from 1.632 to 1.658). Two-sample MR analysis showed that ankle-foot sprains led to a higher risk of falls (OR ​= ​1.036) and a lower fractional anisotropy of superior cerebellar peduncle (SCP) (left, β ​= ​−0.052; right, β ​= ​−0.053). A trend of mediating effect was observed for the fractional anisotropy of right SCP in the causal effects of ankle-foot sprains on falls (β ​= ​0.003). Conclusion: The history of ankle-foot sprains is associated with a slightly increased risk of falls. These findings improve our understanding of the clinical consequences of ankle-foot sprains in terms of fall risk and suggest the importance of adopting more efficient strategies for managing residual functional deficits after the injuries.